PENGARUH MODEL PROJECT BASED LEARNING TERHADAP KEMAMPUAN PASSING BAWAH DALAM PERMAINAN BOLA VOLI PADA SISWA KELAS X SMK N H MOENADI - Dwi Rejeki Utami Utami; Setiyawan; Teguh Santoso; Budi Prasojo (STKIP Subang, 2024)
This study aims to analyze the effect of the Project Based Learning (PjBL) model on the underhand passing ability in volleyball among 10-grade students at SMK N H Moenadi. The research employs an experimental method with a pre-test and post-test design, involving two groups: an experimental group that implements PjBL and a control group that uses conventional teaching methods. Data were collected through tests of underhand passing skills administered before and after the application of the learning model. The findings indicate that the average pre-test score of 36 students was 61.92, while the average post-test score was 84.06, demonstrating a significant improvement between the pre-test and post-test results. The research shows a notable increase in the underhand passing skills of students who participated in PjBL compared to the control group. The implementation of PjBL not only enhances students' technical skills but also fosters collaboration and problem-solving among them. Thus, the PjBL model proves to be effective in improving students' underhand passing abilities in volleyball, providing a more meaningful and relevant learning experience.